2018
DOI: 10.5811/westjem.2017.9.35163
|View full text |Cite
|
Sign up to set email alerts
|

Using Medical Student Quality Improvement Projects to Promote Evidence-Based Care in the Emergency Department

Abstract: IntroductionThe Association of American Medical Colleges’ (AAMC) initiative for Core Entrustable Professional Activities for Entering Residency includes as an element of Entrustable Professional Activity 13 to “identify system failures and contribute to a culture of safety and improvement.” We set out to determine the feasibility of using medical students’ action learning projects (ALPs) to expedite implementation of evidence-based pathways for three common patient diagnoses in the emergency department (ED) se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…22 Many other QI curricula have been developed for trainees with success and positive feedback both from trainees and faculty. 6 , 7 , 23 24 QI competency can be achieved through implementation of an established and systematic curriculum. 7 Prior literature has identified three factors that are critical to establishing a successful curriculum: projects with opportunities for trainees to present and publish, QI-focused or formally credentialed mentors, and projects aligned with institutional goals.…”
Section: Discussionmentioning
confidence: 99%
“…22 Many other QI curricula have been developed for trainees with success and positive feedback both from trainees and faculty. 6 , 7 , 23 24 QI competency can be achieved through implementation of an established and systematic curriculum. 7 Prior literature has identified three factors that are critical to establishing a successful curriculum: projects with opportunities for trainees to present and publish, QI-focused or formally credentialed mentors, and projects aligned with institutional goals.…”
Section: Discussionmentioning
confidence: 99%
“…For example, there is evidence that students can be effective team members of ED quality improvement (QI) projects. In a study of QI initiatives, Manning et al found that with appropriate leadership, third-year medical students could effectively learn about and become effective members of QI teams [16].…”
Section: Discussionmentioning
confidence: 99%
“…We read with great interest Manning et al's recent article on the use of medical student quality improvement projects (QIP) to promote evidence-based care in the accident and emergency (A&E) department (Manning et al, 2018). We believe that students are well positioned to effect change via QI initiatives and offer our experience to support their recommendations, alongside further suggestions to aid implementation and integration of medical student QIPs into clinical practice.…”
mentioning
confidence: 99%